Assessing the role and impact of research in clinical practice among acupuncturists in western countries: a multinational cross-sectional survey - Huemer, Matthias; Graca, Sandro; Bitsche, Sarah; Hofmann, Guenter; Armour, Mike; Pichler, Martin (Frontiers in Medicine, 2024)
Background Evidence-informed practice is crucial to perform safe and efficient health interventions. In recent years, the evidence base of acupuncture continuously increased leading to the integration of acupuncture into clinical guidelines by various leading medical associations worldwide. At the same time, recent studies showed that licensed acupuncturists are rarely utilizing scientific research to inform their practice. Methods This descriptive study using an online survey assessed the role of evidence-informed practice of acupuncturists in Austria, Germany, the United States of America, Australia, and New Zealand and aimed to determine critical factors relevant for promoting research literacy including demographical data, data about the clinical practice patterns, and the role and value of different information sources of traditional, complementary and integrative medicine (TCIM) practitioners. Results In total, 404 acupuncturists completed the online survey that included questions about demographic characteristics, the role and value of research in clinical practice, and details about the amount and type of continuing professional education. Univariate and multivariate analysis was used to determine significant predictors of the outcome variable “importance of research in clinical practice” (numerical rating scale, 0 to 100). The results showed that the majority of acupuncturists use certified courses as primary source of continuing professional education and value experts’ opinions as the most reliable source of information. Multivariate analysis showed that the importance of research is dependent on the interest in research, an interdisciplinary learning environment, and positive experiences with research including if an acupuncture study ever changed the clinical practice of practitioners. Conclusion Future educational programs should therefore focus on an interactive format aiming to promote skills to critically assess the value and practical use of research studies to improve the general practice of acupuncture.